Teresa Wolińska, Justynian Wielki, Wydawnictwo WAM, Kraków 2003, ss. 95+4 nlb. - Kuryłowicz, Marek (Zeszyty Prawnicze, 2017)
Teresa Wolińska, Justynian Wielki, Wydawnictwo WAM, Kraków 2003, ss. 95+4 nlb.